2016
DOI: 10.1139/cjpp-2014-0164
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the anti-ischemia–reperfusion injury effects of ginsenoside Rb1 mediated through the inhibition of p38α MAPK

Abstract: Recent studies have demonstrated that ginsenoside Rb1 protects the myocardium from ischemia-reperfusion (I/R) injury. However, the precise mechanisms for this protection have not been determined. This study aimed to determine whether the attenuation of I/R-induced myocardial injury by ginsenoside Rb1 (GS Rb1) is due to inhibition of p38α mitogen-activated protein kinase (MAPK). Sprague-Dawley rats were distributed among 6 treatment groups: sham group; I/R group; p38 MAPK inhibitor SB203580 group (SB + I/R); GS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Therefore, the expression or activation of TAK1 is an important indicator of the activity of the TGF-β-TAK1-p38MAPK signaling pathway. Several studies have suggested that the p38MAPK pathway is activated in the MI model (5,16) and p38MAPK has become a therapeutic target for heart diseases (17,18). However, other studies have demonstrated the pro-survival function of p38MAPK in MI (19,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the expression or activation of TAK1 is an important indicator of the activity of the TGF-β-TAK1-p38MAPK signaling pathway. Several studies have suggested that the p38MAPK pathway is activated in the MI model (5,16) and p38MAPK has become a therapeutic target for heart diseases (17,18). However, other studies have demonstrated the pro-survival function of p38MAPK in MI (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Coronary atherosclerosis is elicited by a variety of endogenous and exogenous factors through different intracellular signaling pathways (4). MSC transplantation can promote angiogenesis in the infarct area to ameliorate cardiac function in MI (5). However, the clinical application of MSC transplantation is restricted by low survival rates of MSCs following transplantation (6).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, MAPK participated in the regulation of cellular responses to a variety of stimuli, such as mitogens and pro-inflammatory cytokines. Mitogen-activated protein kinases 3, 8 and 14 regulate proliferation, gene expression, cell survival, apoptosis and many other cell functions ( Pearson et al, 2001 ; Li G. et al, 2015 ). The function mechanism of these important proteins might be that they influence the integral network instead of one target alone.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral IR injury is also ameliorated by G-Rb1 activating peroxisome proliferator-activated receptor-γ/heme oxygenase-1 (HO-1) or suppressing protease-activated receptor-1 expression in rat hippocampus [64] , [65] . Moreover, G-Rg1 shows a protective effect against cerebral IR injury by modulating the activation of p38 MAPK [66] . These results suggest that G-Rg1 has therapeutic potential for IR injury.…”
Section: Anti-inflammatory Effects Of Ginsenosidesmentioning
confidence: 97%